'Crowds are mad and criminal': the notion of public order in Italian manuals for police mobile units, 2000–2008. Issue 2 (15th March 2022) - Gargiulo, Enrico
ABSTRACT: The article, moving from a sociological perspective, aims at stressing the ambiguity of the process of democratization of the Italian Republican police by focusing on the notion of public order in Republican Italy and within a Republican model of policing. Towards this end, it focuses not on police practices but on police knowledge in its relationship with concrete police work on the field. In particular, this article analyses the manuals designed for and, between 2000 and 2008, employed in the training of Italian police officers and operators, especially of the mobile units that operate in policing activities dedicated to keeping the public order. By resorting to the tools provided by the critical discourse analysis, special attention is paid to how these texts describe and depict crowds, and how such representations become a device for legitimizing preventive yet repressive interventions. Such interventions take place before potential violent behaviours from demonstrators occur and therefore are not reactive. However, they are not based on mediation and dialogue but rather are coercive, and hinge on a strong use of force.